2022
DOI: 10.1002/cbin.11890
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 suppresses hippocampal neuron apoptosis via the regulation of HIF1α in hypoxia in naked mole‐rats

Abstract: Naked mole-rats (NMRs) (Heterocephalus glaber) are highly social and subterranean rodents with large communal colonies in burrows containing low oxygen levels. The inhibition of severe hypoxic conditions is of particular interest to this study. To understand the mechanisms that facilitate neuronal preservation during hypoxia, we investigated the proteins regulating hypoxia tolerance in NMR hippocampal neurons. Caveolin-1 (Cav-1), a transmembrane scaffolding protein, confers prosurvival signalling in the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Further evidence for CAV1's involvement in limiting ROS production was provided by Chen et al [33]. Similar to how it does in sepsis, hepatic ischemia and reperfusion injury, hypoxia-induced neuronal injury, and acetaminopheninduced cardiovascular injury, CAV1 likewise functions as a brake on apoptosis and ROS [18][19][20][21][22]. It has been demonstrated that CSD peptide, which is derived from CAV1 protein, can be an equivalence to CAV1 and thereby block apoptosis triggered by TGF-β1, hypoxia, or bleomycin [22,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence for CAV1's involvement in limiting ROS production was provided by Chen et al [33]. Similar to how it does in sepsis, hepatic ischemia and reperfusion injury, hypoxia-induced neuronal injury, and acetaminopheninduced cardiovascular injury, CAV1 likewise functions as a brake on apoptosis and ROS [18][19][20][21][22]. It has been demonstrated that CSD peptide, which is derived from CAV1 protein, can be an equivalence to CAV1 and thereby block apoptosis triggered by TGF-β1, hypoxia, or bleomycin [22,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 (CAV1) is an integral membrane protein that serves as the structural basis for caveolae [15]. It is extensively expressed in numerous cells and tissues, and has been implicated in the mitigation of apoptosis through the regulation and control of TGF-β1 signaling, cellular response to hypoxia, in ammation, and oxidative stress [16][17][18][19][20][21][22]. CAV1 expression and α-SMA-positive staining were observed to be signi cantly reduced in cavernous smooth muscle tissue of CNI rats, whereas supplementation of sildena l could mediate the restoration of smooth muscle content by facilitating the regeneration of CAV1 [23].…”
Section: Introductionmentioning
confidence: 99%